Pemberdayaan Santri ZAD IQBS Dalam Menjaga Kebersihan Masjid Di Cianjur - Saputra, Adha; Oki, Alber; Nurzen, Kopri; CH, Taufik; Nurrohman, Izzudin Fahmi (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2023)
This service journal aims to discuss efforts to empower santri in maintaining mosque cleanliness as a form of service to society and religious communities. Mosque cleanliness is an important aspect of maintaining the honour and cleanliness of places of worship in Islam, and the involvement of santri in maintaining mosque cleanliness is a proactive step towards achieving this goal. The results show that involving santri in maintaining the cleanliness of the mosque through the empowerment programme has a significant positive impact. The programme not only improves the cleanliness of the mosque, but also helps to increase the santri's sense of responsibility towards religion and community. In addition, the programme also increases community awareness about the importance of keeping mosques clean.